ChemInform Abstract: Visible Light Mediated Efficient Oxidative Benzylic sp3 C—H to Ketone Derivatives Obtained under Mild Conditions Using O2. Issue 3 (29th December 2015) - Yi, Hong; Bian, Changliang; Hu, Xia; Niu, Linbin; Lei, Aiwen
Abstract: The photooxidation of diarylmethanes (I) in the presence of 9‐mesityl‐10‐methylacridinium perchlorate as a photocatalyst yields benzophenones (II).